2009
DOI: 10.1049/el.2009.0368
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-adjustable clock oscillator based on frequency-to-voltage converter

Abstract: A frequency-adjustable clock oscillator based on a frequency-tovoltage converter is presented. A new architecture is employed without reference frequency input. The system model shows the conditions of system stability. A compensation circuit was used to cancel the variations of frequency over process and temperature. The range of output frequency is from 22.5 -360 MHz, which is within +4.5% variation in worst cases. The circuit was designed in a 0.13 mm CMOS 3.3 V device process, occupying a chip area of abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…However, this comparison is unfair since our results are simulation results and the results in Blauschild (1994), Sebastiano et al (2011aSebastiano et al ( , 2011b are silicon results ( (Sebastiano et al, 2011a(Sebastiano et al, , 2011b with trimming). For a fair comparison, the simulation results of Yi et al (2009) are used to compare with our simulation results, as shown in Table 1. The oscillator in Yi et al (2009) is also carriermobility-based CMOS oscillator, and the CMOS process in Yi et al (2009) is also 0.13 μm CMOS 3.3 V device process.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this comparison is unfair since our results are simulation results and the results in Blauschild (1994), Sebastiano et al (2011aSebastiano et al ( , 2011b are silicon results ( (Sebastiano et al, 2011a(Sebastiano et al, , 2011b with trimming). For a fair comparison, the simulation results of Yi et al (2009) are used to compare with our simulation results, as shown in Table 1. The oscillator in Yi et al (2009) is also carriermobility-based CMOS oscillator, and the CMOS process in Yi et al (2009) is also 0.13 μm CMOS 3.3 V device process.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…For a fair comparison, the simulation results of Yi et al (2009) are used to compare with our simulation results, as shown in Table 1. The oscillator in Yi et al (2009) is also carriermobility-based CMOS oscillator, and the CMOS process in Yi et al (2009) is also 0.13 μm CMOS 3.3 V device process. Table 1 shows that the variation results of the proposed oscillator outperform that in Yi et al (2009).…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations